Cheerleading training uniform design proposal for the University of the Philippines-Diliman pep squad - Noval, Alexandra Frances L.; Lumawig, Maria Josephine T. (Quezon City UP College of Home Economics, 2012)
ABSTRACT This descriptive research proposed a design for a standard cheerleading training uniform for the University of the Philippines Diliman Pep Squad. Through interviews and surveys with purposively selected 61 respondents composed of coaches and members of the team, the study was able to identify the presently used clothing articles during training, the problems encountered by the team members during training caused by presently used clothing, their specific needs and preferences, and the most suitable design features for a cheerleading uniform. Results were summarized in tables where frequency counts and percentage distributions were presented. The findings confirmed a need to develop a standard cheerleading training uniform that can minimize problems encountered during training involving their presently used training attire. Fabric used for the design should be easy to care for, resilient, comfortable, stretchable, slip resistant, has the ability to conceal or repel dirt, lightweight, durable, and dark in color. The basic features for the uniform include a round neck, short sleeves, padding on the shoulder and trunk area, no closures, with a compressed fit, and with a supporting tape along the shoulder and the lower back areas. The researcher recommends continuing this study by implementing and testing the proposed design.
Thesis (BSCT)--University of the Philippines Diliman
Keywords: Sport clothes -- Philippines